Transforming Real Estate Marketing with Augmented Reality Technology - Bhavsar, Mansi Uday; Adisusilo, Anang Kukuh (IC-ITECHS, 2024)
As the world moves toward a more digitally-first environment, the real estate industry is evolving to meet the expectations of today's buyers. People are looking for technologically innovative and entertaining methods to explore properties without leaving the house. This study proposes a cutting-edge virtual tour application based on Augmented Reality (AR) that can transform the tiresome and demanding procedure of seeing properties. Customers may use their smart devices to virtually walk around residences, interact with aspects such as doors and lights, and obtain a 360-degree view of the entire property. The main objective of this research is to demonstrate how AR can reform the real estate industry by replacing expensive static show units with a dynamic, eco-friendly, and globally accessible solution. The app is developed using tools such as Unity 3D, Vuforia SDK, and SketchUp. The research highlights the potential of the app to create a more sustainable marketing approach. It also helps meet the growing demands for a more personalized experience for tech-savvy buyers. Results from the initial testing have shown increased customer engagement and satisfaction levels. The study concludes that integrating AR with property sales can be a very cost-effective, accessible, and scalable alternative with future potential for more enhanced, cross-platform usage, and international reach.